2010
DOI: 10.1007/s00415-010-5812-0
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous pain, pain threshold, and pain tolerance in Parkinson’s disease

Abstract: The mechanisms underlying pain in Parkinson's disease (PD) are unclear. Although a few studies have reported that PD patients may have low pain threshold and tolerance, none could accurately assess whether there was a correlation between sensory thresholds and demographic/clinical features of PD patients. Thus, tactile threshold, pain threshold, and pain tolerance to electrical stimuli in the hands and feet were assessed in 106 parkinsonian patients (of whom 66 reported chronic pain) and 51 age- and sex-matche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
1
4

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 19 publications
3
75
1
4
Order By: Relevance
“…It is characterized by two different neurological responses towards the pain stimuli: (i) a first phase, starting immediately after injection of formalin, and responding to the local stimulation of nociceptors, and (ii) a second phase occurring later in time and reflecting the response of the central nervous system towards the stimulus, especially the spinal cord. PD patients display chronic unexplained pain and a decrease in pain tolerance [37], [44]. We therefore expected the Tg mice to show an increase of the pain sensitivity following the injection of the formalin in the paw, and in particular in the second phase, which is considered as a chronic response [34].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by two different neurological responses towards the pain stimuli: (i) a first phase, starting immediately after injection of formalin, and responding to the local stimulation of nociceptors, and (ii) a second phase occurring later in time and reflecting the response of the central nervous system towards the stimulus, especially the spinal cord. PD patients display chronic unexplained pain and a decrease in pain tolerance [37], [44]. We therefore expected the Tg mice to show an increase of the pain sensitivity following the injection of the formalin in the paw, and in particular in the second phase, which is considered as a chronic response [34].…”
Section: Discussionmentioning
confidence: 99%
“…Currently only indirect evidence suggested nociceptive system dysfunction in patients with PD. The study by Zambito and colleagues [26] adds information on how PD can put patients at higher risk of pain than healthy subjects. Using electrical stimulation they assessed tactile threshold, pain threshold, and pain tolerance in 106 PD patients (66 of whom had chronic pain).…”
Section: Pathophysiologymentioning
confidence: 99%
“…A major finding of the study was that significant differences with respect to gender, geographic distribution, and age (tables 1, 4) were similar to those reported by Marcus et al [20], who found that pain, fatigue, and psychiatric complaints were more commonly reported in women. Reduced pain thresholds and tolerance [5,19,21] and/or increased responses to pain stimuli were observed in females [22]. Schestatsky et al [19] and Brefel-Courbon et al [11] discovered that during off-periods, patients with PD and central pain had a lower threshold for pain caused by thermal stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…This controversy might be related to the potential effect of dopamine on pain inhibition pathways. Since at least one of the cortically based descending pain inhibitory pathways is partially dopaminergic (rostral agranular insular cortex) [18], the dopaminergic denervation indicates a higher level of pain and suggests that the causes of pain might be related to movement disorders as well as the loss of dopaminergic neurons in the substantia nigra [18] and arise from central basal ganglia dysfunction [5,19]. Evidence has shown an increased incidence of nondystonic or musculoskeletal pain and pain relief experienced by the patient subsequent to levodopa therapy as well as an increased pain threshold observed during the on-period [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation